A Rare Case of Idiopathic Congenital Complete Heart Block in a Neonate - Sinha, R; Negi, V; Dalal, SS (Journal of Nepal Paediatric Society, 2012)
Congenital complete heart block in utero has become diagnosed more frequently with the clinical use of fetal echocardiography. Autoimmune-associated congenital complete heart block (CHB) is a rare but important disease that can now be diagnosed in utero using fetal echocardiography1,2,3,4. The overall incidence of isolated CHB has been reported to be approximately 1:15,000 to 20,000 live births5. Several reviews have shown that children diagnosed prenatally have an increased mortality compared to those diagnosed immediately after birth or later in childhood1,2,3,4. At birth, some neonate with complete heart block may remain asymptomatic and may not require a pacemaker but majority require pacemaker to increase the heart rate. We report a rare case of idiopathic congenital complete heart block in a newborn male. J Nepal Paediatr Soc 2012;32(2):163-165 doi: http://dx.doi.org/10.3126/jnps.v32i2.5992